Creator Governance in Social Media Entertainment. (November 2019) - Cunningham, Stuart; Craig, David
This article addresses the platformization of cultural production by offering a creator-centric account of industrial and governance issues in social media entertainment (SME). SME is our term for the emerging industry of native online cultural producers together with the platforms, intermediaries, and fan communities operating interdependently, and disruptively, alongside legacy media industries and across global media cultures. The central concern of the article is that these creators are not recognized as stakeholders in current debates both academic and policy on platform governance. The relationship between the platform behemoths and individual creators may seem grossly disproportionate, but insights from network economics suggest a more supple account of power. The interests of creators are examined in the "top-down" context of the exercise of platform governance and efforts, by platforms and the state, to improve it. Those interests are also canvassed from the "bottom up"—how creators and creator advocacy are organizing and acting collectively to improve prospects for creators in this emerging industry.